The effect of processing on the short- and long-term viability of epididymal African buffalo (Syncerus caffer) spermatozoa - Van Leeuwen, Maira Margaretha (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.